Islam Nusantara; Sebuah Kajian Post Tradisionalisme dan Neo Modernisme - Abdul Basid (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2017)
Islamic Nusantara is not new religion, not just the new thought. Islamic Nusantara is the approach resourches of transcendent scientific which have religion character and then mergered by humanism sciences resourches which have humanism character. Islamic nusantara culture hoped became scientific resouches and culture inheritance which resourched form local wisdom Indonesian people that mixed between transcendent approach and local wisdom aprroach . Islamic Nusantara not just born from tradition, that the tradition became new power which rested on the power of society and constructed by sciences and knowledge and became morality power as the first bollard. These paper will explain the thought of The Islamic Nusantara as post traditionalism and neo modernism studied.